The implementation of enhanced recovery after surgery (ERAS) in complex spinal surgery - Angus, Michelle (J Spine Surg, 2019)
BACKGROUND: This paper aims to review the introduction of an enhanced recovery after surgery (ERAS) service within complex spinal surgery, with an aim to assess if this is a cost effective way to improve the overall experience of such complex surgery. METHODS: The ERAS model was defined and followed within a regional centre for complex spinal surgery in the UK. Outcomes such as length of stay (LOS) and satisfaction were measured before and after implementation of the service. RESULTS: LOS was reduced and both patient and staff satisfaction improved following the implementation of the ERAS service. CONCLUSIONS: The ERAS model can successfully be implemented within complex spinal surgery, to help improve satisfaction and reduce cost.